Corporate Responsibility and Corporate Governance in Europe - Luca Bisio (Symphonya, 2003)
The policies adopted by multinationals have generated some rather harsh criticism due to the insensitivity shown with regard to the environment, food safety and social marginalisation. This is due to the fact that excess supply conditions, which now characterize the richer markets, have forced companies into a ‘neo-liberalism’ spiral. The strong dynamism exhibited by corporations in taking advantage of the opportunities offered by globalisation, contrast with the inadequacy of institutions (and, in particular, of Nation-States). Basically, it becomes more and more difficult for Nation-States to build bridges between the global system and local socioeconomic systems.